Legal Balance: Where Parental Obligations and Responsibilities Lie in the Current Legal Landscape Concerning Gender-affirming Treatments for Transgender Minors in the United States and the United Kingdom - Huang, Fuhong (Transactions on Social Science, Education and Humanities Research, 2024)
This research paper critically examines the regulatory role of legislation in governing parental responsibility concerning gender-affirming treatments for transgender minors in the United States and the United Kingdom. Drawing on secondary sources, including legal frameworks, human rights conventions, and scholarly articles, the study explores the complex dynamic between state control and parental autonomy in decision-making processes regarding the well-being of transgender minors. Findings reveal a concerning trend in the United States, with an increasing number of states implementing restrictions on gender-affirming care for minors. In contrast, the United Kingdom has made significant strides in transgender rights, yet uncertainties persist regarding their application to minors. Striking the right balance is crucial, as excessive state control may hinder access to vital treatments, jeopardizing the mental health and overall well-being of transgender minors. Conversely, granting unchecked parental autonomy may expose vulnerable youth to potential abuse or future regrets. Thus, the research underscores the necessity of carefully crafted legislation that safeguards the rights and well-being of transgender minors, ensuring decisions are made in their best interests while respecting parental responsibilities. This study contributes to the ongoing discourse on legal frameworks surrounding gender-affirming treatments for transgender minors, highlighting the importance of finding a balanced approach that protects the rights and well-being of this vulnerable population.